?IRRADIATION OF PINK BOLLWORM LARVAE BY Co-60 AND Cs-137 SOURCES AND THEIR EFFECTS ON VIABILITY, REPRODUCTIVITY AND STERILITY OF SUBSEQUENT PI AND FIPROGENY (Biological Sciences - PJSIR, 1994)
The irradiation of mature (cut out) larvae at 35 Gy from Co-60 and Cs-137 resulted in reduced and delayed pupation. Co-60 caused significantly more lethality than Cs-137. The fecundity of the females both PI and FIemerging from irradiated mature larvae was drastically reduced for Co-60 as well as for Cs-137 treatment. The female moths were comparatively more prone to gamma radiation damage than the males. Larval survival and adult emergence were dose dependent following irradiation of mature pink bollworm larvae at40-65 Gy from Cs-137 alone. The fecundity of mature PI and FI progeny and percent of males in FI generation reduced with the increased doses. Complete sterility was recorded in crosses treated male x treated female (fMxTF) at all doses. The effect oflarval irradiation on mature progeny of F, adults was also reduced in crosses involving either FI males or FI females. The doses tested for mature larvae were too high and are not suitable for the control of pink bollworm through FI sterility.